Efficacy of Multiple Micronutrients Fortified Milk Consumption on Iron Nutritional Status in Moroccan Schoolchildren - Imane El Menchawy; Asmaa El Hamdouchi; Khalid El Kari; Naima Saeid; Fatima Ezzahra Zahrou; Nada Benajiba; Imane El Harchaoui; Mohamed El Mzibri; Noureddine El Haloui; Hassan Aguenaou (Journal of Nutrition and Metabolism)
Iron deficiency constitutes a major public health problem in Morocco, mainly among women and children. The aim of our paper is to assess the efficacy of consumption of multiple micronutrients (MMN) fortified milk on iron status of Moroccan schoolchildren living in rural region. Children (N=195), aged 7 to 9 y, were recruited from schools and divided into two groups: the nonfortified group (NFG) received daily a nonfortified Ultra-High-Temperature (UHT) milk and the fortified group received (FG) daily UHT milk fortified with multiple micronutrients including iron sulfate. Blood samples were collected at baseline (T0) and after 9 months (T9). Hemoglobin (Hb) was measured in situ by Hemocue device; ferritin and C Reactive Protein were assessed in serum using ELISA and nephelometry techniques, respectively. Results were considered significant when the p value was <0.05. At T9 FG showed a reduction of iron deficiency from 50.9% to 37.2% (p=0.037). Despite the low prevalence of iron deficiency anemia (1.9%); more than 50% of children in our sample suffered from iron deficiency at baseline. The consumption of fortified milk reduced the prevalence of iron deficiency by 27% in schoolchildren living in high altitude rural region of Morocco. Clinical Trial Registration. Our study is registered in the Pan African Clinical Trial Registry with the identification number PACTR201410000896410.